The Relation Between Compassionate Love and Prejudice: The Mediating Role of Inclusion of Out-Group Members in the Self. (March 2016) - Sinclair, Lisa; Fehr, Beverley; Wang, Wan; Regehr, Elise
Recently, there has been an increase in prejudice toward some groups such as immigrants. In response, governments and citizens have called for compassion. In four studies, we tested the hypothesis that people who are high in compassionate love would express less prejudice than those who are low. We found that people high in compassionate love had more positive attitudes toward out-groups, including immigrants. The relation between compassionate love and prejudice toward immigrants was mediated by inclusion of out-group members in the self. An experiment provided evidence of a causal link between compassionate love and prejudice toward immigrants. Finally, people high in compassionate love were less likely to discriminate against immigrants in a budget cutting exercise and more likely to volunteer to help them. Empathy did not account for our results. We conclude that compassionate love holds promise as a positive pathway to prejudice reduction.